2008
DOI: 10.2486/indhealth.46.550
|View full text |Cite
|
Sign up to set email alerts
|

Energy Absorption of Seated Occupants Exposed to Horizontal Vibration and Role of Back Support Condition

Abstract: Occupational off road vehicle drivers are exposed to considerable magnitudes of whole-body vibration (WBV), which is known to cause discomfort, annoyance, and several health and safety risks. Many studies have suggested strong association between the exposure to WBV and low back pain 1,2) . The vast majority of the studies on human responses to vibration have emphasized the exposure to vertical WBV, since heavy on-road and off-road vehicles are believed to transmit relatively higher magnitudes of vertical vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
8
25
0
Order By: Relevance
“…The VPA responses of the seated occupants exposed to single and three-axis vibration revealed very low values in the 0.5 Hz frequency band suggesting rigid system like behaviour of the seated human body, which is consistent with the reported studies [15][16][17][18][19]. The total VPA values of the seated occupant exposed to single axis fore-aft, lateral and vertical vibration increased with the rms acceleration magnitudes of vibration (Table 3) in a nearly quadratic manner, which is again consistent with the reported studies [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The VPA responses of the seated occupants exposed to single and three-axis vibration revealed very low values in the 0.5 Hz frequency band suggesting rigid system like behaviour of the seated human body, which is consistent with the reported studies [15][16][17][18][19]. The total VPA values of the seated occupant exposed to single axis fore-aft, lateral and vertical vibration increased with the rms acceleration magnitudes of vibration (Table 3) in a nearly quadratic manner, which is again consistent with the reported studies [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that the exponent is around 2 and 1.8-2.8 under vertical and horizontal vibration, respectively [17,19].…”
Section: Energy Absorption Of Seated Body Exposed To Single and Threementioning
confidence: 99%
“…It has been shown that the proposed W d -weighting correlates reasonably well with the biodynamic responses of the body seated without a back support 4) . The biodynamic responses of the occupants seated with a back support and exposed to fore-aft WBV, however, differed significantly from those corresponding to sitting with a back support and exposed to lateral vibration 1,3,4,6,8) . The characterisation of biodynamic responses of the body seated assuming typical driving postures (back and hands supports) is thus essential for defining adequate frequency weightings for exposure assessments.…”
Section: Introductionmentioning
confidence: 82%
“…The lower frequencies under higher magnitude of vibration were attributed to the softening effect of the human body [1][2][3][4] . The STHT responses revealed relatively lower magnitudes but comparable resonant frequencies with increase in the magnitude of vibration (Table 4).…”
Section: Effect Of Excitation Magnitudementioning
confidence: 99%
See 1 more Smart Citation